Lesson learned from the 'DUCH' trial : a comprehensive review of the first case before the Extraordinary Chambers in the Courts of Cambodia - Kelsall, Michelle Staggs; Baleva, Mary Kristerie A.; Nababan, Aviva ([Phnom Penh] : East-West Center, 2009)
"The Asian International Justice Initiative is a collaborative project between the East-West Center, Honolulu and the University of California, Berkeley War Crimes Studies Center. The Initiative's Khmer Rouge Tribunal Monitoring Program was established in 2008, to facilitate ongoing analysis and regional dialogue about the proceedings before the Extraordinary Chambers in the Courts of Cambodia. The report provides a comprehensive review of the Court's first case, Prosecutor vs Kaing Guek Eav, alias 'Duch". It is the culmination of ten months' work form the Program's Monitoring Group."--Cover p.[4]
Keywords: Kaing Guek Eav alias Duch, -- 1942-2020 -- Trials, litigation, etc; Extraordinary Chambers in the Courts of Cambodia; Trials (Crimes against humanity) -- Cambodia; Trials, litigation, etc; Cambodia -- History -- 1975-1979